A Evaluation of Gastrointestinal Causes of Recurrent Abdominal Pain in Children - MUHAMMAD ARSHAD ALVI, IQTADAR SEERAT (Journal of Fatima Jinnah Medical University, 2018)
Aims &Objective: To evaluate GIaetiology of recurrent abdominal pain in children with and without alarm symptoms Study Design: Retrospective study. Place and Duration of Study: This retrospective study was conducted for the time period starting from February, 2016- February, 2017 at the department of Paediatric Gastroenterology, Hepatology& Nutrition, KFSH&RC, Jeddah, Saudi Arabia. Materials and Methods: 25 children were recruited in this study with history of recurrent abdominal pain. Out of 25 there were 17 children with alarm symptoms and 8 without alarm symptoms. The referrals were made from different specialities of our department and also from a number of local hospitals outside Jeddah. Results: Out of 17 patients with RAP and alarm symptoms there were 3 cases (17.5%) of reflux oesophagitis, 1 case (5.8%) of eosinophilicoesophagitis, 10 cases (59%) of Crohn’s disease, 1 case (5.8%) of chronic gastritis and2 cases (11.7%) of irritable bowel syndrome were diagnosed. In 8 children without alarm symptoms there were 2 cases (25%) of H.Pylori gastritis, 2 cases (25%) of Crohn’s disease and 1 case (12.5%) of coeliac disease. The diagnosis of irritable bowel syndrome was made in rest of 3 patients (37.5%). Conclusion: Majority of children with alarm symptoms were diagnosed with organic diseases. Children with ongoing recurrent abdominal pain without alarm symptoms were also found to have organic causes. Therefore children of recurrent abdominal pain even without alarm symptoms should also be investigated and managed by Paediatric gastroenterology team due to high prevalence of underlying organic diseases to avoid any delay.